(untitled) (Al-Academy, 2024)
The Transformation of environments surrounding human which called (place), formed an intermediate compresser in forming awareness pictures, human knowledge, culture and thought features, and changing the systems and contexts of human societies, which led to a change the rhythm of life as a whole. So according to that the place will be encodes according to these data for psychological connotations, lead to human sense of harmony with the place in different manner format, here the search problem lies when trying to detect how Iraqi artist deliberating with the place concept, wondering how to investing place in the contemporary Iraqi drawing within its reference dimension, and showing mechanisms from comparative study for the works of two artists, who formed the place element a radical axis in their works, how are each of the artist Nuri al-Rawi, and the artist Saad al-Tai. And the place within the data human culture and thought, represents civilizational reference and national privacy, and the art dimension is a part of data of human culture and thought. So it carries a great mutants for the place. Hence the importance of research comes to be as a new dimension on the level of critical analysis to detect the references and attributes of this concept in the identity of Iraqi art. So the search aims: to detect referential dimension of place in the Iraqi drawing among contemporary contexts, and showing it in the work of artists Nuri al-Rawi and Saad al-Tai. Based on the correlation of both - knowledge and place, for that each of this knowledge founded its theories about the concept of place, both according to its data and orientations, as the problem of the place is from philosophical problems which be placed within the circle of simple search even to be impossible of the same place, but the concept of the place was more fortunate in the field of philosophical studies in general, and monetary and literary and artistic especially, so had to stand starting from the concept of the place, and the theory of place in art and literature from the perspective of aesthetic and semantic, of where correlation between place and time for literary space with creativity space. On this basis, many descriptions developed for the place types, correlated with the most important concepts within the dialectic forming place within the field of fine arts, which are include: real place, symbolic place, assumption place, and imagined place. And then shed light on the mechanisms represent the place in trends of modern art (global and Iraqi), which varied from symbolic realistic representation for inherited significances reaching to absent the place or neglect its recipes and breakdown from domination imposed by its selected, or attempt to openness to the space of place in the work, which skips the boundaries of time and history.After analyzing the samples that have been chosen are intentional, came researcher outcome of the most important: that the place manifestation different levels of expression at each of the artist Al-Rawi and artist Al-Tai, the Rawi was often clings to supposed place, while Tai moved from supposed place to symbolic place to the imagined place, the Al-Rawi often transcend on the realistic to place and transmit them to places with ideal characteristics, while Al-Tai transmitting recipes of example on the landscape seems to be linked to reality. And the place for Rawi reflects oftenly an externally part (village), but for Tai reflecting external parts and internal (special and private). The place devoid of all that is emotive in Al-Rawi, so its place are rapting meditating, while Al-Tai places are more emotive and movement from Al-Rawi places. In addition to the general results included the concept of place and its relationship with characteristics of the formation of the artwork.